Factores de riesgo relacionados en la hiperplasia prostática benigna en mayores de 50 años en el Hospital Martin Icaza, periodo junio – octubre 2023 - Arteaga Balseca, Cristhofer Patricio (2023)
Benign prostatic hyperplasia is one of the most common conditions that occur in men after the age of 40 years. It is an enlargement of the prostate gland that appears with age and by stimulation of testosterone in which benign nodules produce an increase in the size of the prostate gland without progressing to cancer. As age increases, so does the risk of developing BPH, which affects 9 out of 10 men. The complications of this disease deteriorate the quality of life of the person, because he can develop urinary conditions such as: urinary obstruction, repeated urinary infections, renal failure and even hydronephrosis. The goal of treatment is to improve symptoms and quality of life, prevent clinical progression of the disease and reduce the risk of complications or the need for surgery. The research raises the modifiable and non-modifiable risk factors of this pathology is evidenced in patients who attended the Hospital Martin Icaza, it was determined that the risk factors were high prolactin level within the groups of higher and lower risk, age groups over 50 years, race, family history, comorbidity (hypertension and diabetes mellitus) and harmful habits (alcoholism and smoking). The research proposes the modifiable and non-modifiable risk factors of this pathology is evidenced in 65 patients who attended the Martin Icaza Hospital in the period June - October, within the age groups over 50 years, race, family history, comorbidity (hypertension and diabetes mellitus) and harmful habits (alcoholism and smoking). The work was structured as follows: chapter I presents the approach of the study, the problem statement, problem formulation, objective, justification of the research and the hypothesis. Chapter II presents the background of the research and theoretical bases. Chapter III presents the methodology. Chapter IV presents the budget and timetable.